O método discursivo de leitura no ensino de língua portuguesa: por um leitor da historicidade do texto - Gomes, Glaucio Ramos (2017)
In the universe of theorists who reflect on the reader's formation in the school, it is common sense the understanding that a reader does not form in a single instant nor by the singular action of a given theory. On the contrary, the reader is always a process in formation that occurs through the integrated action of various theoretical segments that are experienced in the classroom. Within the range of theoretical-methodological procedures that are thought as tools to aid the formation of the reader, we use the French Speech Discourse Analysis which, given its interdisciplinary character, is allied to other areas of knowledge. In this sense, authors like Pêcheux (1997, 2008, 2009), Foucault (1995, 2007, 2008), Orlandi (2006, 2010, 2012), Lerner (2002), Chartier (2002) and Martins (AD), as a reading methodology, could help in the formation of the reader. As for the specific objectives, we have to: a) Evaluate the Reading proposal applied by the teacher to understand the theoretical-methodological particularities of the discursive reading mediation; B) Analyze the result of the discursive reading mediation, from the confrontation between the initial and final questionnaires, to observe the effects of the AD proposal on students' reading gestures .; C) To understand how the classroom, with its dynamics and hierarchical organization, acts in the process of docilization of the subject-student and in the constitution of the governability of the teacher; D) Understand how power relations, and real wills interfere with teacher and student reading gestures. In order to carry out the research, we conducted a discursive mediation of reading with students from the ninth grade of elementary school, from a public school, taking as an object of analysis exemplary cordel literature. The corpus of the research is fragmented into two parts: cordel copies for the investigation of representations of man and woman from the Northeast in the speech of the cord; Transcription of the discursive mediation of reading lived in the classroom. The analysis of the cords was performed so that we could construct the didactic sequence for the discursive reading mediation. The results of this analysis show that the discourse of the cords we select builds a social representation that disparages Northeastern man and woman. Regarding the analysis of the discursive reading mediation, the results show that the DA has, in fact, a contribution to give to the practices of reading in the classroom. The contribution is that it enables the student to work with the discursive dimension of the language. In this work, he will consider, for the construction of reading, the socio-ideological interferences of saying that it is always accompanied by non-sayings that act on the said, sliding the meaning; You will realize that under the evidence of given meaning there are other possible meanings. In addition, by experiencing a discursive reading, the student can see the language in its political dimension, that is, language as a social construct based on real wills that are structured by the action of power.